Changes and Trend Disparities in Life Expectancy and Health-Adjusted Life Expectancy Attributed to Disability and Mortality From 1990 to 2019 in China - Chen, Lijun; Wang, Lu; Qian, Yun; Chen, Hai (Frontiers in Public Health, 2022)
Objective: We aims to investigate sex, age and cause-specific contributions to changes and trend disparities in life expectancy (LE) and health-adjusted life expectancy (HALE) attributed to disability and mortality from 1990 to 2019 in China, which provides insight into policy-making, health systems planning and resource allocation. Methods: Contributions of disability and mortality to changes and trend disparities in LE and HALE were estimated with standard abridged life table, Sullivan’s method, and decomposition method, using retrospective demographic analysis based on mortality and years lived with disability (YLD) rates extracted from Global Burden of Disease Study 2019 (GBD 2019). Results: From 1990 to 2019, LE and HALE increased by 10.49 and 8.71 years for both sexes, mainly due to NCDs (5.83 years, 55.58% for LE and 6.28 years, 72.10% for HALE). However, HIV/AIDS & sexually transmitted infections had negative effects on changes in LE (-0.03 years, -0.29%) and HALE (-0.05 years, -0.57%). Lung cancer and ischemic heart disease caused the biggest reduction in LE (-0.14 years, -1.33%) and HALE (-0.42 years, -4.82%). And cardiovascular diseases (-0.08 years, -0.92%), neurological disorders (-0.08 years, -0.92%), diabetes and kidney diseases (-0.06 years, -0.69%) and transport injuries (-0.06 years, -0.69%) had main negative disability effects in HALE. Moreover, life expectancy lived with disability (LED) increased by 1.78 years, mainly attributed to respiratory infections and tuberculosis (1.04 years, 58.43%) and maternal and neonatal disorders (0.78 years, 43.82%). Conclusion: LE and HALE in China have grown rapidly over the past few decades, mainly attributed to NCDs. It is necessary to further reduce the negative mortality effect of HIV/AIDS, lung cancer, colon and rectum cancer, pancreatic cancer and ischemic heart disease and the negative disability effect of stroke, diabetes mellitus and road injuries. In addition, the signs of disparities in mortality and disability of different sexes and ages call for targeted and precise interventions for key groups such as males and the elderly. According to the decomposition results, we may better determine the key objects of health policies that take into account substantial cause-specific variations to facilitate the realization of "healthy China 2030" plan.